England Through Colonial Eyes in Twentieth-Century Fiction - Blake, A. author. aut Link
X, 207 p.
Keywords: Much attention has focused on the imperial gaze at colonised peoples, cultures, and lands. But, during and after the British Empire, what have writers from those cultures made of England, the English, and issues of race, gender, class, ethnicity, and desire when they have travelled, expatriated, or emigrated to England? This question is addressed through studies of the domestic novel and the Bildungsroman , and through essays on Mansfield, Rhys, Stead, Emecheta, Lessing, Naipaul, Emecheta, Rushdie and Dabydeen.